Proporsi Konsumsi Junk Food dan Status Gizi Berlebih di Mahasiswa Kedokteran - Bestari Yuniah; Fajar Awalia Yulianto (Bandung Conference Series: Medical Science, 2023)
Abstract. Overnutrition status in Indonesia has increased, from 14.8% (2013) to 21.8% (2018). The cause of excess nutritional status is an excessive intake of junk food. Current technological advances make it very easy to consume junk food through online food delivery services. Students consume junk food through online food delivery services, which has been increasing during the Covid-19 pandemic. The purpose of this study was to examine the Relationship between Junk Food Consumption through Online Food Delivery and Overnutrition Status among Students of the Faculty of Medicine, Islamic University Bandung. This study used a cross-sectional design approach. This research was conducted in January-December application for 62 respondents. The technique of sampling in this study used a stratified random sampling technique. The data were analyzed by the Fisher's Exact test. The results showed that students who often consumed junk food (83.9%) were more than people who didn’t consume junk food (16,1%). In the group which contains students who consume junk food, the proportion of excess nutritional status (100%) was greater than the group that rarely consumed junk food (30%). Efforts need to be made to increase awareness of controlling food orders through online food delivery to maintain a balanced nutritional intake. Keywords: Junk food, medical faculty students, online food delivery, overnutrition status Abstrak. Status gizi berlebih di Indonesia mengalami peningkatan, dari 14,8% (2013) menjadi 21,8% (2018). Faktor penyebab status gizi berlebih yaitu asupan makanan junk food yang berlebih. Kemajuan teknologi saat ini sangat memudahkan untuk mengonsumsi junk food melalui layanan online food delivery. Mahasiswa mengonsumsi junk food melalui layanan online food delivery yang semakin meningkat di masa pandemi Covid-19. Tujuan penelitian ini adalah untuk meneliti Hubungan antara Konsumsi Junk Food Melalui Layanan Online dengan Status Gizi Berlebih pada Mahasiswa Fakultas Kedokteran Universitas Islam Bandung. Penelitian ini menggunakan pendekatan dengan design cross sectional. Penelitian dilakukan pada Januari‒Desember 2022 terhadap 62 responden. Pengambilan sampel pada penelitian ini menggunakan teknik stratified random sampling. Data dianalisis dengan menggunakan uji Fisher’s Exact. Hasil penelitian menunjukan bahwa mahasiswa yang sering mengonsumsi junk food 83,9% lebih banyak dibandingkan dengan yang jarang mengonsumsi junk food 16,1% dimana dalam kelompok yang sering mengonsumsi junk food persentase status gizi berlebihnya 100% lebih besar dibandingkan kelompok yang jarang mengonsumsi junk food 30%. Perlu dilakukan upaya-upaya untuk meningkatkan kesadaran mengontrol pemesanan makanan melalui online food delivery untuk menjaga asupan gizi seimbang. Kata kunci: Junk food, mahasiswa fakultas kedokteran, online food delivery, status gizi berlebih